1999
DOI: 10.1034/j.1399-0039.1999.540101.x
|View full text |Cite
|
Sign up to set email alerts
|

The CBF.78 monoclonal antibody to human sialophorin has distinct properties giving new insights into the CD43 marker and its activation pathway

Abstract: We confirm here the CD43 specificity of the CBF.78 monoclonal antibody (mAb) and compare its phenotypic and functional capacities to classical group-A mAbs (DFT1, MEM-59) and to 2 other CD43 mAbs (RDP/AD9, 161-46). It reacts with stable human CD43 transfectants in a sialic acid independent way and blocks completely cell binding of RDP/AD9 or 161-46 more or less but not DFT1 and MEM-59. Its distribution differs from all other CD43. B lymphocytes, but surprisingly the majority of granulocytes or monocytes are CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…There are previous reports indicating that CD43 molecules may also have accessory involvements in T cell activation, such as, for example, in mice, where CD43 mAb appears to costimulate T cell activation during treatment with plastic-bound CD3 mAb and alloantigens (17,40). In humans, however, there does not appear to be any evidence of CD43 mAb being involved in a costimulatory capacity in the polyclonal activation of T cells (41). In situations involving Ag-specific responses, there is one report that CD43 is necessary for the production of IL-2 in HLA class II-specific human hybridoma T cells (42), but it is important to note that the experimental system used to obtain these data was an unusually artificial one.…”
Section: Discussionmentioning
confidence: 98%
“…There are previous reports indicating that CD43 molecules may also have accessory involvements in T cell activation, such as, for example, in mice, where CD43 mAb appears to costimulate T cell activation during treatment with plastic-bound CD3 mAb and alloantigens (17,40). In humans, however, there does not appear to be any evidence of CD43 mAb being involved in a costimulatory capacity in the polyclonal activation of T cells (41). In situations involving Ag-specific responses, there is one report that CD43 is necessary for the production of IL-2 in HLA class II-specific human hybridoma T cells (42), but it is important to note that the experimental system used to obtain these data was an unusually artificial one.…”
Section: Discussionmentioning
confidence: 98%
“…However, when the data reported here are considered in more detail, this view does not seem to be correct. The CD43 mAbs, which do induce aggregation (161-46, HI161, MEM-59, and 84-3C1), all recognize the 110-kDa isoform [30]. Some of the mAbs (e.g., 148-1C3 and RPD/AD9) that recognize neuraminidase-sensitive epitopes, the most negatively charge portions of CD43, did not induce homotypic clustering.…”
Section: Discussionmentioning
confidence: 99%
“…Since previous studies have identified tyrosine phosphorylation as a downstream event in CD43-induced signaling [29,30,36], the next experiments explored this question. The results are shown in Fig.…”
Section: Cd43 Induces Rapid Tyrosine Phosphorylation and Tyrosine Phomentioning
confidence: 99%
“…(18). In fact, it has been reported that many of the anti-CD43 monoclonal antibodies can recognize glycosylated fraction of CD43 molecule (4,6,13,14,19,20).…”
Section: Flow Cytometric Analysis In Various Cell Linesmentioning
confidence: 99%